Gulls foraging in landfills: Does atmospheric exposure to halogenated flame retardants result in bioaccumulation?. (February 2021) - Sorais, Manon; Spiegel, Orr; Mazerolle, Marc J.; Giroux, Jean-François; Verreault, Jonathan
Highlights: Atmospheric exposure vs. bioaccumulation of flame retardants was studied in gulls. Greatest liver flame retardant levels were found in gulls foraging in landfills. Positive associations were found between atmospheric exposure and bioaccumulation. Foraging behaviors in landfills did not influence flame retardant bioaccumulation. Abstract: Several bird species have adapted to foraging in landfills, although these sites are known to represent significant sources of emissions of toxic semi-volatile chemicals including the halogenated flame retardants (HFRs) (e.g., polybrominated diphenyl ethers (PBDEs) and emerging compounds). The objective of this study was to investigate the association between atmospheric exposure to PBDEs and selected emerging HFRs and their bioaccumulation in landfill-foraging birds. We determined HFR concentrations in liver of 58 GPS-tagged ring-billed gulls (Larus delawarensis) breeding in a colony near Montreal (Canada) as well as their atmospheric exposure determined using a miniature bird-borne passive air sampler. PBDE mixtures were the most abundant HFRs determined in passive air samplers (daily exposure rates of ∑9 PentaBDE: 47.4 ± 6.5 pg/day; DecaBDE: 36.0 ± 6.3 pg/day, and ∑3 OctaBDE: 3.4 ± 0.5 pg/day) and liver (∑9 PentaBDE: 68.1 ± 8.9 ng/g ww; DecaBDE: 52.3 ± 8.1 ng/g ww, and ∑3 OctaBDE: 12.8 ± 2.1 ng/g ww), and their concentrations increased with the presence probability of gulls in landfills. We found a spatial relationship between the local sources of atmospheric exposure to PBDEs and the sites associated with greatest PBDE concentrations in liver. Specifically, the atmospheric exposure index was correlated with the bioaccumulation index (Pearson r for ∑9 PentaBDE: r = 0.63, p < 0.001; DecaBDE: r = 0.66, p < 0.001, and ∑3 OctaBDE: r = 0.42, p < 0.001). However, we found no correlation at the individual level between daily exposure rates of HFRs in passive air samplers and their liver concentrations. This suggests that complex exposure pathways combined with toxicokinetic factors shaped HFR profiles in gull liver, potentially confounding the relationships with atmospheric exposure.